Training of Trainers (ToT) youth in improving healthy quality of healthy livingin the city of Medan - Yustina, Ida; Sentosa, Heru; Sudaryati, Etti (Talenta Publisher, 2019)
The problems faced by partners in community service locations are teenagers in the majority of research sites who are obese, and students in schools do not understand how to behave in a healthy life. During adolescence there is rapid growth and development both in terms of physical, psychological and intellectual. In supporting adolescent growth, nutritional adequacy is needed. Nutrient component requirements include: energy, protein, and other micronutrients which have increased significantly. Adolescent life is not only centered on one thing, the challenges currently faced by adolescents today range from relationships, physical health, mental health, child marriage and others. This dedication activity aims to create youth cadres who understand health, later after this activity is carried out, young people are expected to be agents of change in their environment both within the school, home and community. This Training of Trainers activity is held for 2 days with reference to modules that have been prepared specifically for adolescents. This activity is formulated with games that have objectives in accordance with the material presented. The number of participants who attended the training were 30 participants who were in high school. The training of trainers is expected to increase knowledge, raise awareness and be able to inform health in the school, family and community environment.